Correlation Study Of Intelligence With Mental Health Issues Among Gifted And Talented Students - Ahmad Faiz Yazid; Abdul Razzak Khan Rustum Ali Khan; Nur Fazidah Asmuje; Amirah Zainun; Nor Adlyizan Theis (Institut Penyelidikan Pembangunan Belia Malaysia, 2024)
Edisi Khas Yours’18 Agenda Sosial Vol 2